Wireless access point with location based awareness / Mohd Izuddin Ibrahim - Ibrahim, Mohd Izuddin (Faculty of Computer and Mathematical Sciences, 2007)
The declining cost of mobile computing devices, wireless devices and the rapidly increasing in number of wireless networks and there is increasing interest in the development of location aware applications. These applications include context aware systems to collect or disseminate information, robotics, duress alarms in institutions such as universities and hospitals. There are many technologies that may be used to sense the location of mobile devices or personnel, including those based on infrared, ultrasonic, radio frequency tags and magnetic sensing. Most of these technologies require the deployment of devices specifically placed to support the location system. This paper focuses on a location system based on the Radio- Frequency (RF) of packets on the wireless network. This technique has the great advantage that it may be implemented using off the shelf hardware that is generally already deployed to support the data network.The primary function is to locate and track the wireless devices, which is connected to the access point in real-time and their activities and attributes are captured, logged and reported.